Comparing migration of Whinchats Saxicola rubetra from the non-breeding grounds in Liberia and Nigeria: Differences due to geography but otherwise very similar - Will Cresswell; Rob Patchett; Emma Blackburn; Malcolm Burgess (PLoS ONE, 2025)
Migrant birds in the Afro-Palearctic region are declining, so understanding general migration characteristics, such as site use, connectivity, and phenology is crucial for their conservation. We tracked 64 whinchats Saxicola rubetra, a declining Palearctic-breeding passerine, from non-breeding sites in Nigeria and Liberia, to Europe and back, in multiple years. We predicted differences, resulting from the geographical location of the two non-breeding sites, in location of respective breeding areas (migratory connectivity), number of non-breeding and stopover sites, migration distance and duration, degree of loop migration and phenology. But we predicted similarities, resulting from optimising migration behaviour, in migration leg distance duration, and stopover duration. Liberian tagged birds bred mainly in central and northern Europe, with Nigerian birds mainly in eastern Europe. Migratory spread was large resulting in range overlap and low connectivity. About 25% of whinchats used more than one sub-Saharan non-breeding site, their location dependent on geographic availability. Liberian birds had longer migrations in distance and duration, and more stopovers, but only Nigerian birds showed a statistically significant difference in longitude comparing spring and autumn migrations (i.e., a clear loop migration). Nigerian birds departed later than Liberian birds, independent of breeding latitude or migration distance, although latitude determined arrival time for breeding. Spring migration leg distance and stopover duration, and all leg durations, were similar for both populations; but Nigerian birds had longer duration stopovers and shorter distance migration legs in autumn. Whinchats were shown to have varied migration routes and characteristics, with a variable pace of migration that allows them between 50 and 75% of daylight hours to rest and forage, but with major stopover duration possibly being affected by site quality. One whinchat moved from sub-Saharan non-breeding site to northern European breeding site in 7 days, and 8% of complete migration durations were 14 days or less. This suggests whinchats are well adapted to the current variable geography and so may have the capacity to adapt to potential climate change across Europe and West Africa, although average quality and availability of stopover sites may be contributing to declines.